ENSAYO DE DIFERENTES TIPOS DE CONTENEDORES PARA Q.ILEX, P.HALEPENSIS, P.PINASTER Y P.PINEA: RESULTADOS DE VIVERO - DOMÍNGUEZ LERENA, S; HERRERO SIERRA, N; CARRASCO MANZANO, I; OCAÑA BUENO, L; PEÑUELAS RUBIRA, J L (II Congreso Forestal Español, 1997)
The influence of 16 of the most commonly utilised containers on seedling characteristics of Quercus ilex, Pinus pinea, P. halepensis and P. pinaster have been analysed. Studied plant features -height, diameter, shoot and root dry weight, and number of branches- were correlated with container dimensions. Observations on sorne practical problems in several containers and their suitability for forest plant production are given.
Keywords: calidad de planta; desarrollo; envases; sistemas radicales